Potential shared pathogenic mechanisms between endometriosis and inflammatory bowel disease indicate a strong initial effect of immune factors - Zhang, Haolong; Mo, Yaxin; Wang, Ling; Zhang, Haoling; Wu, Sen; Sandai, Doblin; Shuid, Ahmad Naqib; Chen, Xingbei (Frontiers in Immunology, 2024)
Over the past decades, numerous studies have demonstrated a common immune dysregulation between endometriosis (EM) and Inflammatory Bowel Disease (IBD).However, the underlying pathological mechanisms remain unknown. In this study, bioinformatics techniques were used to screen large-scale gene expression data for plausible correlations at the molecular level in order to identify common pathogenic pathways between EM and IBD. 113 differentially expressed genes (DEGs) that were co-expressed in EM and IBD have been identified, comprising 28 down-regulated genes and 86 up-regulated genes. Five hub genes (SERPING1、VCAM1、CLU、C3、 CD55) were identified through the Protein-protein Interaction network and MCODE.Area Under the Curve (AUC) values, indicating that they have predictive ability for disease occurrence. These hub genes could be used as potential biomarkers for the development of EM and IBD. Our findings indicated a shared pathogenic mechanism between EM and IBD relating to immune regulation and cell signaling. This research provides novel avenues for preventing and treating above conditions.